Gamo Society Vernacular House Typologies and Their Science, Southern Ethiopia - Choto, Habte Mengistu (American Scientific Research Journal for Engineering, Technology, and Sciences, 2013)
The main purpose in this study is to identifying house typology & their science in Gamo society, southern Ethiopia. It provides facts about the vernacular houses of the society. Types are identified without looking in to architectural detail, ornament, building materials and construction techniques. In determining house typologies, generally only the core or main part of the house is considered; small side wings, rear service (or extensions) later additions, and attached outbuildings usually are not taken in to account.  A case study which is supplemented with a qualitative research method was conducted from Nov./2012-Jan./2013. The case study was done in one year by taking 57 sample vernacular house typologies from 42 Deres/communities/. Data were collected using qualitative methods, Capturing images, videos and as well as observation. After clearing and checking for consistency data was grouped, edited, coded and analyzed.The result shows in Gamo society three major vernacular house typologies; Waje, Kara and Yara, were identified based on their shape, function, method of construction and construction material they used. And the result of this study showed that Gamo society is inter-related with their vernacular houses.